Nature of Ribosome-Bound β-Galactosidase - Bronskill, Patricia M. (1971)
Properties of the ribosome-bound β-galactosidase were examined in Escherichia coli cells after prolonged induction. This fraction of enzyme was not chased from ribosomes by removal of inducer, or by treatments with hydroxylamine, puromycin, chloramphenicol, and azide. However, the metabolic turnover of this fraction could be demonstrated by means of a pulsed exposure to the phenylalanine analogue β-2-thienylalanine, and this fraction was enriched in heavy forms relative to the soluble enzyme. These observations indicated a tight coupling of the release of ribosome-bound enzyme to nascent enzyme synthesis, and it is suggested that the ribosome-bound enzyme is related to an intermediate stage in the assembly of quarternary enzyme structures.